Advances in dynamically controlled catalytic reaction engineering. Issue 12 (21st October 2020) - Armstrong, Cameron D.; Teixeira, Andrew R.
Abstract : Dynamically forced input oscillations exhibit ability to surpass classical thermodynamic barriers through reactor operation and surface resonance. Abstract : Transient reaction modulation has found its place in many branches of chemical reaction engineering over the past hundred years. Historically, catalytic reactions have been dominated by the impulse to reduce spatial and temporal perturbations in favor of steady, static systems due to their ease of operation and scalability. Transient reactor operation, however, has seen remarkable growth in the past few decades, where new operating regimes are being revealed to enhance catalytic reaction rates beyond the statically achievable limits classically described by thermodynamics and the Sabatier principle. These theoretical and experimental studies suggest that there exists a resonant frequency which coincides with its catalytic turnover that can be exploited and amplified for a given reaction to overcome classical barriers. This review discusses the evolution of thought from thermostatic (equilibrium), to thermodynamic (dynamic equilibrium), and finally dynamic (non-equilibrium) catalysis. Natural and forced dynamic oscillations are explored with periodic reactor operation of catalytic systems that modulate energetics and local concentrations through a multitude of approaches, and the challenges to unlock this new class of catalytic reaction engineering is discussed.